Practical Exploration of Ideological and Political Construction in Youth Social Work Courses - Yue, Lijun (Journal of Social Science and Humanities, 2025)
This study aims to address the urgent need for ideological and political education in colleges and universities in the new era. Addressing current challenges in the “Youth Social Work” course, such as fragmented ideological and political elements, homogenized teaching plans, and disconnected case studies, this study conducts a systematic exploration of ideological and political education in the curriculum to enhance its educational effectiveness. The study follows a “theoretical construction - practical development - summary and promotion” approach. Through literature research, policy interpretation, and interviews with teachers and students, a systematic matrix of “course knowledge points - ideological and political elements” was constructed, resulting in a “Course Ideological and Political Education Elements List.” Subsequently, core teaching modules were selected and, based on the principle of “integrating professional knowledge with value guidance,” the teaching objectives, content, and methods were restructured to develop a “Core Teaching Module Ideological and Political Education Integration Plan.” Finally, closely aligned with social issues and local culture, a “Course Ideological and Political Education Case Collection” was developed, reflecting both contemporary and professional characteristics. This practical exploration has yielded a replicable and scalable ideological and political education teaching resource package, including a systematic “Element List,” a modular “Integration Plan,” and a contemporary “Case Collection.” Practice has proven that this approach effectively addresses the disconnect between ideological and political education and professional teaching, significantly enhancing the curriculum’s value-oriented function and the effectiveness of practical teaching. This practical exploration successfully established a model for the ideological and political development of youth social work courses characterized by “systematic exploration, modular integration, and case-based implementation.” This approach provides a viable solution for cultivating interdisciplinary social workers with both solid professional qualities and a deep sense of patriotism. It also holds significant reference and promotional value for the ideological and political reform of courses in similar humanities and social sciences disciplines.